Representati Lima Nilai Utama dalam Karakter Miguel Rivera dalam Coco (2017) Produksi Disney - Artini, Ni Nyoman; Suwastini, Ni Komang Arie; Utami, IGA Lokita Purnamika; Sanjaya, Komang Angga Surya (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2025)
Character education values are frequently presented in animated movies. While many values can be identified from one character in a movie, the present study highlights the five core values proposed by the Ministry of National Education in the characterization of Miguel Rivera from Disney’s Coco (2017). The present study employed textual analysis to identify the representation of character education values. Data analysis was conducted simultaneously with the data collection, data reduction, data display and conclusion drawing. The analysis revealed that Miguel Rivera’s characterizations reflect the traits of religiosity, nationalism, independence, integrity, and mutual cooperation. Because the movie is centered around the conflict of Miguel Rivera’s passion to sing and play Mexican guitar and set around the Mexican celebration of Day of the Dead, Miguel Rivera’s adherence to the ritual of the Dead, his pride in the Mexican music and food strongly reflects his religious and nationalist values. His struggle about lying to his family, Ernesto de la Cruz, and Enrique Rivera shows his integrity. Furthermore, his kindness in helping others and his handwork to achieve his goal presented his cooperative values. These findings imply that children’s movies could give examples of character values by presenting visual images of how the characters’ actions.